The effect of loading rate on characteristics of type II twin boundary motion in Ni-Mn-Ga. (February 2018) - Zreihan, Noam; Faran, Eilon; Shilo, Doron
Abstract: We measure the velocities of type II twins in Ni-Mn-Ga over four decades by force-driven pulsed magnetic tests and displacement-driven mechanical tests. Mechanical tests reveal that the twinning stress is a rate-sensitive property, and imply that displacement-driven twin boundary motion follows similar kinetics to those measured under force-driven conditions. All probability density plots of twin boundary velocities demonstrate normal distributions around an average value determined by the kinetic relation. The relative standard deviation of the measured histograms decreases monotonously with increasing velocity. The results imply that the kinetic relation is a valid input for modeling the actuation performance of Ni-Mn-Ga. Graphical abstract: